Hyperflexion and Femoral Interference Screw Insertion in ACL Reconstruction. Issue 8 (6th August 2018) - Steiner, Mark E.; Wing, David; Walley, Kempland C.; Manoukian, Ohan; Perez-Viloria, Miguel; Okajima, Stephen; Nazarian, Ara
Background: In anatomic anterior cruciate ligament (ACL) reconstructions produced with flexible reamers and no knee hyperflexion, it is unknown whether knee hyperflexion is necessary for femoral interference screw insertion. Purpose: To compare femoral screw-graft divergence in anatomic ACL reconstructions with endoscopic interference screws placed without knee hyperflexion and with the use of flexible versus rigid screwdrivers. Study Design: Controlled laboratory study. Methods: Ten matched pairs of cadaveric knees had bone-tendon-bone graft ACL reconstructions with anatomic femoral tunnels. The knees were flexed to 90°. Femoral interference screws (7 × 20 mm) were placed in pairs of knees: in 1 knee with a flexible screwdriver and in the opposite knee with a rigid screwdriver. Graft-screw divergence was imaged with computed tomography scans and tested with cyclic and static biomechanical tests. Results: The mean screw-graft divergence was 12.07° ± 4.04° with the rigid screwdriver and 10.68° ± 3.23° with the flexible screwdriver ( P = .35). The cyclic tests with screws placed by a rigid screwdriver had a mean increase in displacement of 0.56 ± 0.20 mm. For screws placed with the flexible screwdriver, the mean increase in displacement was 0.58 ± 0.32 mm ( P = .66). Yield load was 393.3 ± 95.1 N for screws placed by a rigid screwdriver and 408.2 ± 119.0 N for screws inserted with the flexible screwdriver ( P = .78). Maximum load was 523.1 ± 88.7 N for screws placed by a rigid screwdriver and 467.1 ± 107.3 N for screws inserted with the flexible screwdriver ( P = .09). Conclusion: With either a rigid or a flexible screwdriver, there were no significant effects on screw divergence or fixation strength. Clinical Relevance: Knees can be kept at 90° during endoscopic femoral interference screw insertion. The use of a traditional rigid or flexible screwdriver will not affect screw-graft divergence or fixation strength.